Assessment of contact interface on seismic response of tunnels by the modified response acceleration method. (May 2023) - Zhou, Tonglai; Li, Shuang; Fu, Zhipeng; Dong, Changsong
Abstract: The contact interface of the tunnel with composite lining will affect the seismic response of the tunnel. It is necessary to study the effect of interface properties on the seismic response of the tunnel, including the tunnel with buffer layer and without buffer layer. Initially, the establishment of the finite element (FE) model is introduced in detail, including the convergence-confinement method and the tracking element method. Then, a modified response acceleration method (MRAM) is proposed and verified, and it is proved to be accurate and convenient. Finally, based on the MRAM, the influence of the contact interface on the seismic response of the tunnel is studied, including the tunnel with buffer layer and without buffer layer. At the same time, different PGA and buffer layer thickness are considered. The results show that the property of the contact interface significantly affect the seismic response of the tunnel, including the internal force and tensile damage of the tunnel. Moreover, PGA and buffer layer thickness also change the relationship between interface properties and tunnel seismic response. The ideal interface properties (no-slip and full-slip) will greatly increase or decrease the seismic response of the tunnel. The proposed MRAM and conclusions about the contact interface can provide a reference for the seismic design of the tunnel.